2014
DOI: 10.1371/journal.pone.0097543
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Emotional, Behavioral, and Social Difficulties in the Danish Population of Children and Adolescents with Type 1 Diabetes – Results of a National Survey

Abstract: ObjectiveTo assess the prevalence of psychological difficulties in Danish children and adolescents with type 1 diabetes using both child/adolescent and caregiver reports, and to investigate associations between these symptoms and metabolic control, adherence, and quality of life.Research Design and Method:A total of 786 children and adolescents (8–17 years) recruited through the Danish Registry of Childhood Diabetes completed subscales of the Beck's Youth Inventories (BYI-Y), while 910 caregivers completed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 43 publications
1
47
0
Order By: Relevance
“…HbA1c levels were significantly higher in families where the child was the only family member participating in the study. In addition, no significant differences were observed between those responding and those initially agreeing to participate but whose answers were missing, whereas HbA1c levels were higher in those who did not agree to participate …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HbA1c levels were significantly higher in families where the child was the only family member participating in the study. In addition, no significant differences were observed between those responding and those initially agreeing to participate but whose answers were missing, whereas HbA1c levels were higher in those who did not agree to participate …”
Section: Resultsmentioning
confidence: 99%
“…This validation study is part of a national web‐based survey performed in 2009 that included 1997 Danish children and adolescents (aged from 2 to 17 years) with T1D. The study aimed to assess the influence of several psychosocial variables (including family functioning) on glycemic control, adherence to treatment, and quality of life . Data collection was conducted in collaboration with the Danish Society for Diabetes in Childhood and Adolescence and the national database DanDiabKids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was conducted in 2009 as part of a nationwide websurvey that included all 1997 Danish children and adolescents (2-17 years) with T1D. 13,19,20 It contained 15 different questionnaires (including SEDM) and assessed the influence of psychosocial variables on adherence, glycemic control, and QoL and was conducted in collaboration with the Danish Society for Diabetes in Childhood and Adolescence, which administers the Danish Registry for Childhood and Adolescent Diabetes (DanDiabKids). This registry contains information dating back to 1996 on every child and adolescent with T1D in Denmark.…”
Section: Overall Designmentioning
confidence: 99%
“…The relationship between the clinical outcome parameter HbA1c concentration, as an indicator for the glycemic target, and HRQL has also been investigated in young patients with diabetes mellitus. While some studies, found no associations between HRQL and glycemic target (21)(22)(23), others were able to detect a relationship between both the two outcome parameters (24)(25)(26)(27). For example, it was found that higher scores in HRQL were associated with better metabolic control (25), while poor metabolic control was related to psychosocial problems in children and adolescents with T1DM (12,27).…”
Section: Introductionmentioning
confidence: 99%